COLLABORATIVE LEARNING THROUGH FEEDBACK IN EFL WRITING CLASS AN ACTION RESEARCH - Murti, Mira Nissa (2013)
The research was aimed at identifying the use of peer feedback to improve students' skills in writing narrative texts and investigating students' responses toward peer feedback in assessing narrative texts in eleventh graders by using classroom action research method. The research consisted of three cycles which involved 39 students from one of the senior high schools in Bandung as the participants. The data were collected through observation, teacher's diary, questionnaires and students' written texts. The findings showed that peer feedback could improve students' skills in writing narrative text in which the average score increased from cycle one to cycle three which was from 69 to 89.5. It showed that 95% of the students achieved above the targeted average score (78) in cycle three. Furthermore, 77% of the students liked the implementation of peer feedback in writing narrative texts. Keywords: peer feedback, writing narrative.